The taxation of illegal income in South Africa: the basis on which proceeds from a unilateral taking should be taxed - Nyakanyanga, Kudzai Talent (Rhodes University, Faculty of Commerce, Department of Accounting, 2017)
In South Africa, income tax is levied in terms of the Income Tax Act, 58 of 1962, and the calculation of a taxpayer's taxable income and ultimately the tax liability commences with considering what constitutes the taxpayer's gross income. In terms of the definition of "gross income" a person can be taxed either on receipts or accruals. The definition makes no reference, however, to the legality of receipts or accruals. The main issue addressed in this thesis is the interpretation of the term "receipt" in relation to the proceeds from a unilateral taking (theft) and whether the concept of a receipt in relation to theft should be interpreted using the subjective approach used in MP Finance Group CC (In Liquidation) v C:SARS, or the objective approach. An interpretative research approach was used to provide clarity on the matter. The documentary data used for the research consists of South African tax legislation, case law, textbooks and journal articles. The thesis also analysed SARS' view in Interpretation Note 80 that MP Finance Group CC (In Liquidation) v C:SARS is authority for a unilateral taking being a receipt, and the correctness of this viewpoint. A brief comparative analysis was done of the basis on which illegal income flowing from a unilateral taking is taxed in Australia, New Zealand and America. These countries have legislative provisions that specifically deal with how the proceeds from theft in the hands of a thief should be treated for tax purposes. The thesis concludes that, although the court in MP Finance Group CC (In Liquidation) v C:SARS shed some light on the issue of the taxability of income from illegal activities, the basis on which proceeds from theft may be taxed, as opposed to the basis on which proceeds from other illegal activities like fraud are taxed, remains a grey area in our law. The thesis recommends the introduction of a legislative provision in order to provide a more unified, consistent and effective approach when taxing all illegal income.
Keywords: Uncatalogued